2013
DOI: 10.1017/cbo9781139107860
|View full text |Cite
|
Sign up to set email alerts
|

The Handbook of Journal Publishing

Abstract: The Handbook of Journal Publishing is a comprehensive reference work written by experienced professionals, covering all aspects of journal publishing, both online and in print. Journals are crucial to scholarly communication, but changes in recent years in the way journals are produced, financed, and used make this an especially turbulent and challenging time for journal publishers - and for authors, readers, and librarians. The Handbook offers a thorough guide to the journal publishing process, from editing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 91 publications
0
29
0
2
Order By: Relevance
“…Thatcher quoted in Skinner et al, describes the editorial function as 'the key to all of this: that's what makes this publishing' [38]. This would allow the Press to have better control over publications and to identify new opportunities [30].…”
Section: Staffingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thatcher quoted in Skinner et al, describes the editorial function as 'the key to all of this: that's what makes this publishing' [38]. This would allow the Press to have better control over publications and to identify new opportunities [30].…”
Section: Staffingmentioning
confidence: 99%
“…A programme level planning model would help to develop a publishing policy, which would in turn help to develop publication level planning; the what, how and why of the publishing process [30]. The Press has a golden opportunity to define a set of targeted publications around the post-2014 REF.…”
Section: Assessing the Value Of The Pressmentioning
confidence: 99%
“…Others, such as "Open Access Publishing and Scholarly Societies: A Guide," stress the need for author agreements, but do not cover the need to provide users with copyright information (Velterop, 2005). The Handbook of Journal Publishing (Morris et al, 2013) includes a chapter titled "Copyright and Other Legal Aspects," which has the following to say about copyright information presented to readers:…”
Section: Tools and Guidance Around Copyright And Journal Publishingmentioning
confidence: 99%
“…However, they remain a major funding stream for some smaller publishers, particularly among American-based not-for-profit organisations and learned societies [15]. There are also disciplinary differences; a 2012 survey of major journals found that page charges are substantially more common in the sciences than social sciences, and within the sciences are most frequent in computer science and astronomy-though this may be linked to the dominant publishers in those fields being non-profit rather than commercial [16].…”
Section: A Survey Of Publishing Chargesmentioning
confidence: 99%
“…Many journals (particularly in medicine, biology, and geology [17]) also supplemented their income by selling large volumes of reprints of articles; with the general switch to online access, this is becoming rarer, as the demand for paper reprints has been displaced by easily-circulated PDFs [15].…”
Section: A Survey Of Publishing Chargesmentioning
confidence: 99%